GAMBARAN KEPEMIMPINAN DI RUMAH MAKAN PADANG DJUANG - Dian Juliarti Bantam; Salwa Sakila; Adinda Nadhira Ruhul Zahidah; Elita Lismanaji Zavisty (LPPM Universitas Proklamasi 45, 2024)
This research discusses the role and influence of leadership in daily operations in the culinary industry, with a focus on Padang Djuang restaurants. In this context, leadership is considered a key factor influencing service quality, customer satisfaction and overall performance. This research uses qualitative methods with a phenomenological approach. This research aims to identify the role of leadership and understand the concept of leadership in the context of the culinary industry, especially Padang Djuang restaurants. The results of the analysis show that the dominant leadership style in Padang Djuang restaurants is participative leadership, where restaurant owners and employees apply a democratic approach in decision making. This is reflected in the active involvement of employees in the strategic decision-making process, which strengthens the relationship between leaders and team members and creates an open and transparent work atmosphere. In addition, the use of a task-oriented leadership style is also found in the clear division of roles and responsibilities among employees, creating a structured and efficient organizational structure. Despite this, leaders still maintain their authority by providing clear direction and ensuring that all decisions are in line with the company's vision and goals. From the results of this research, understanding and applying effective leadership principles is very important for the operational success of Padang Djuang restaurants. The resulting recommendations include the importance of strengthening a participative culture in leadership, improving communication and collaboration between owners, managers and employees, and considering market needs and desires in strategic decision making. By paying attention to the findings and recommendations from this research, it is hoped that Padang Djuang restaurants can continue to develop and maintain their position as one of the leading culinary destinations in Indonesia.